Correlation between interalar width and intercommisural width against mesiodistal width of central upper incisor in Buginese tribe - Bahruddin Thalib; Ayu Saputri (DiscoverSys Inc., 2016)
Various types of anatomical landmarks of the face should match its proportions with the size of the teeth which is the interalar width, intercomissural width, interpupillary width, Intercanthal width, and byzigomatic width. Some of face landmarks can be used as a guide in the selection of anterior teeth in complete denture, especially if the pre extraction record such as radiography image, extracted teeth, model study, the remaining teeth, face shape, and the shape of the curved jaw have been lost. The objective of this study was to evaluate the correlation between interalar width and intercommisural width against mesiodistal incisivus centralis width in a group of Buginese tribe. Ninety nine Buginese tribe subjects aged 17-25 were selected. The interalar width, intercommisural width, and mesiodistal incisor centralis teeth were measured using caliper about three times for accuracy and precision. Mean of interalar width and mesiodistal incisor centralis maxilla width in males more width than females (p<0.05), and intercommisural width in females more width than males (p>0.05). The degree of correlation between interalar width against mesiodistal incisor centralis maxilla width was 0.030, -0.246, 0,225 in Buginese tribe, males, and females (p>0.05). : The degree of correlation between intercommisural width againstÂ mesiodistal incisor centralis maxilla width in Buginese tribe was 0,054, 0,013, 0,153 in Buginese tribe, males, and females (p>0.05). The degree of correlation between interalar width and intercommisural width was 0.301 and 0.356 in Buginese tribe and males (p<0.05), and 0,281 in females (p>0.05). In conclusion, there is no significant correlation between interalar width and intercommisural width against mesiodistal incisor centralis maxilla width in a group of Buginese tribe. Interalar width and intercommisural widthÂ directly proportional to mesiodistal incisor centralis maxilla in a group of Buginese tribe. Interalar width and intercommisural widthÂ inversely proportional to mesiodistal incisor centralis maxilla in males and directly inversely in females.